Risk characterization of Escherichia coli and Listeria monocytogenes as pathogens of concern in produce safety - Manville, Erin (Kansas State University, 2022)
Both Escherichia coli and Listeria monocytogenes represent a challenge for produce safety. Through the years, the causal agent of several fresh produce foodborne outbreaks has been traced back to irrigation water systems contaminated with E. coli. Rising concerns regarding the safety of agricultural water has led to the implementation of governmental preventative regulation and investigations into how irrigation water systems are getting contaminated with E. coli. At the same time farm and produce operations offer ideal conditions for L. monocytogenes. This organism has become a top threat to the fresh produce industry with numerous routes of direct and indirect contamination due to its persistence and biofilm forming abilities. The produce industry needs to understand how to effectively combat both E. coli and L. monocytogenes to reduce the chances of fresh produce related foodborne outbreaks. Therefore, the objectives of this study were as follows: 1) characterize E. coli from irrigation water in Kansas and Missouri through Whole-Genome Sequencing; 2) analyze the attachment and formation of L. monocytogenes biofilms on different surfaces; and 3) evaluate the effectiveness of single and simultaneous applications of UV-C light and sanitizers against L. monocytogenes biofilms. For objective 1: quarterly water samples collected from five farms in Kansas and Missouri were filtered using the EPA Method 1603. Presumptive E. coli were then confirmed by polymerase chain reaction (PCR) before undergoing whole-genome sequencing (WGS). Further analysis was conducted in-silico to understand serotype, Antimicrobial Resistant (AMR) genes, virulent genes, source of contamination, and phylogenetic relationships. Results indicate the presence of 99 different serotypes, all samples had at least two AMR genes, and four isolates were found to be Shiga-toxin producing. More than half of the isolates collected (53%) could be traced back to a bovine source of contamination. Objective 2 included the use of a Center for Disease Control and Prevention (CDC) biofilm reactor to grow multi-strain L. monocytogenes biofilms on wood, nylon, and polycarbonate coupons at 20±2˚C. Biofilm formation and attachment was evaluated through a rinse assay while cell hydrophobicity was completed using the standard sessile drop technique. Wood coupons were the most hydrophilic surface (~35˚) and overall cells exhibited significantly greater attachment to nylon (P<0.05). Finally, objective 3 was aimed to test the effectiveness of sanitizers, after biofilm growth. Individual applications of UV-C light or a chemical sanitizer as well as the simultaneous application of a chemical sanitizer and UV-C light were studied. Following treatment, coupons were neutralized, and remaining cells enumerated. Material (wood, nylon, and polycarbonate) were found to play a significant role in the efficacy of sanitizers (P<0.05) with the most effective treatment (up to 4 log CFU/cm² reduction) being the simultaneous application of UV-C light and 5% silver citric acid (P<0.05). The results obtained in this research underline the importance of agricultural water sources and environmental conditions when assessing produce safety. It also provides an initial understanding of L. monocytogenes biofilms and their response to the use of UV-C light and chemical sanitizers to effectively control this pathogen in produce processing environments.
Keywords: Escherichia coli; Listeria monocytogenes; Biofilms; Irrigation water